Efficacy and safety of suprascapular nerve block combined with axillary nerve block for arthroscopic shoulder surgery: A systematic review and meta-analysis of randomized controlled trials. (October 2021) - Zhao, Jinlong; Xu, Nanjun; Li, Jiahui; Liang, Guihong; Zeng, Lingfeng; Luo, Minghui; Pan, Jianke; Yang, Weiyi; Liu, Jun
Abstract: Background and aims: A variety of peripheral nerve block methods are used in the clinic to enhance the effect of postoperative analgesia. In recent years, an increasing number of surgeons have considered the efficacy and safety of suprascapular nerve block (SSNB) combined with axillary nerve block (ANB) for controlling perioperative pain in shoulder arthroscopy. The purpose of this study was to compare the efficacy and safety of SSNB + ANB and interscalene block (ISB) versus SSNB alone for shoulder arthroscopic surgery. Study design: Systematic review; Level of evidence, 1. Methods: The protocol for this meta-analysis is registered with PROSPERO (CRD42021254008). PubMed, Cochrane Library, Embase and CNKI were searched for RCTs from inception to April 30, 2021. A meta-analysis was performed with Review Manager 5.3 to calculate the RR or WMD of related outcome indicators. Results: Nine RCTs involving 543 cases from 5 countries were included. Compared with SSNB alone, SSNB + ANB was more effective at pain relief at 6, 12, 24, 36 and 48 h postoperatively. In terms of patient satisfaction score, scores for SSNB + ANB at 12 (WMD = 2.01, 95% CI = 0.25 to 3.78) and 24 (WMD = 1.68, 95% CI = 0.11 to 3.24) hours after the operation were higher than those of SSNB alone, but there was no significant difference at 36 and 48 h postsurgery. There was no significant difference in pain score between SSNB + ANB and ISB at 6 and 12 h after surgery or in patient satisfaction at 24 h (WMD = 0.13, 95% CI = −0.36 to 0.63) postsurgery between SSNB + ANB and ISB. In terms of safety, compared with ISB, SSNB + ANB reduced the incidence of dyspnea (RR = 0.25, 95% CI = 0.09 to 0.68). Conclusions: Compared with SSNB alone, SSNB + ANB has better advantages regarding pain relief and patient satisfaction within 24 h after surgery. Compared with ISB, SSNB + ANB shows no difference in postoperative pain relief or patient satisfaction, but SSNB + ANB can reduce the incidence of dyspnea more than ISB. Highlights: Compared with SSNB, SSNB + ANB has better advantages regarding pain relief and patient satisfaction within 24 h after surgery. Compared with ISB, SSNB + ANB shows no difference in pain relief or patient satisfaction, but can reduce the dyspnea. Regarding opioid consumption, there is still a lack of clinical data to compare the advantages of SSNB + ANB versus ISB.